Effects of Al2O3 and LiAlO2 Co-coating on electrochemical properties of LiNi0.8Co0.1Mn0.1O2 cathode materials. Issue 10 (15th May 2023) - Wang, Jiatai; Zhao, Duan; Zhou, Geng; Wei, Shishi; Hou, Shunli; Li, Yuanyuan; Ma, Hongbin; Yuan, Ya; Yan, Xiaocen; Hou, Xiaoyi
Abstract: Lithium-ion batteries are widely used in aerospace, power vehicles, portable electronic devices and other fields because of their environmental friendliness, rechargeable cycle and high energy density. The nickel-cobalt-manganese ternary materials with high nickel has high specific discharge capacity and is regarded as one of the most promising cathode materials. However, with the increase of the number of cycles, the cycle performance becomes worse and the specific capacity decays sharply. In this work, Al2 O3 and LiAlO2 were coated on the surface of NCM811 by combining ball milling mixing and solid-phase synthesis to prepare the AL-NCM811 cathode material. The coating thickness formed by Al2 O3 and LiAlO2 was 10–70 nm, which effectively improves the cycle stability and rate performance of NCM811 material. When charged and discharged at 0.1C, the first discharge specific capacity and capacity retention rate after 100 cycles of 0.5AL-NCM811 were 196.26 mAh/g and 96.47%, respectively, while those of NCM811 were only 193.78 mAh/g and 72.18%, respectively. When the current density was 5.0C, the discharge specific capacity of 0.5AL-NCM811(139.16 mAh/g) was 55.368 mAh/g higher than that of NCM811(83.80 mAh/g).